2006
DOI: 10.11606/issn.1678-4456.bjvras.2006.26471
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da integridade cromatínica de espermatozóides de galos (Gallus gallus, Linnaeus, 1758) de linhagem pesada em duas idades

Abstract: Na avicultura, a avaliação de fertilidade em machos é de extrema importância, para garantir uma melhor produção de ovos férteis. As técnicas para avaliação de fertilidade em galos são pouco exploradas, sendo que na maioria das vezes, a avaliação é feita por amostragem e levando em consideração, apenas fatores morfofisiológicos, diretamente relacionados com o espermatozóide. Mas é sabido que, em outras espécies, além dos fatores morfofisiológicos, existem problemas intrínsecos ao espermatozóide, como a baixa co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
4
1
1
Order By: Relevance
“…In case of changes in chromatin structure, morphologic abnormalities are expected [3,10,11]. However, some studies have shown that sperm containing abnormal chromatin condensation do not necessarily present morphologic changes, requiring morphologic analysis followed by evaluation of the internal structure [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In case of changes in chromatin structure, morphologic abnormalities are expected [3,10,11]. However, some studies have shown that sperm containing abnormal chromatin condensation do not necessarily present morphologic changes, requiring morphologic analysis followed by evaluation of the internal structure [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A semen sample was collected from each box on the day the treatments started, that is, when the roosters were 52-wk-old, and another sample 6 wk later, when they were 58-wk-old. A drop of semen from each sample was placed into a microtube containing 1.5 mL of formaldehyde saline ( Soares and Beletti, 2006 ) and sent to the Reproductive Biology Laboratory of the Federal University of Uberlândia for chromatin analyses. Therefore, using cloacal massage ( Wilson, 1988 ), 12 samples were collected from each group (6 samples before and 6 samples after the experimental period), totaling 48 samples.…”
Section: Methodsmentioning
confidence: 99%
“…The techniques of fertility research in roosters are little explored, most of the time, performed by sampling and considering only morphological and motility factors, not being routinely evaluated for sperm chromatin ( Soares and Beletti, 2006 ). Several methods to identify changes in sperm chromatin have been tested, being sperm chromatin structure assay ( SCSA ) the most frequently used to analyze rooster semen ( Partyka et al, 2010 ; Salehi et al, 2020 ; Shabani et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A teoria da estratificação pode explicar os resultados obtidos no trabalho, onde quanto mais velhos os espermatozoides penetrando a membrana perivitelina, menor a fertilidade encontrada. Soares e Beletti (2006) (BELETTI, 2013). Dessa forma, estudos posteriores são necessários para verificar as alterações que ocorrem nos espermatozoides enquanto armazenados nos TAE após a inseminação e que podem interferir na formação embrionária.…”
Section: Avaliação No Incubatóriounclassified